ANALISIS PERUBAHAN PENUTUPAN KAWASAN HUTAN MANGROVE DI KECAMATAN LANGSA BARAT KOTA LANGSA TAHUN 1990, 2000 DAN 2015 - Dikky Setiawan; Anita Zaitunah; Samsuri Samsuri (Peronema Forestry Science Journal, 2016)
Mangrove forest is tropical coastal vegetation communities. Mangroves play  important role for the life of coastal society, because it can protect the coast from the storm and tsunami. This research is aimed to identify mangrove cover change and calculate area of mangrove in forest sub-district of West Langsa, Langsa regency in 1990, 2000 and 2015. The research method was used a supervised classification with maximum likelihood classifier. Image interpretation use monogram of West Langsa. The research found change of mangrove land cover in the period 1990 - 2000  become a swamp of 308.45 Ha. Within period 2000 – 2015, the land cover of mangrove area changed to be the swamp which approximately 191.38 ha. The mangrove area of West Langsa sub-district is 1.191,93 hectares (29.90%) in year 1990, 1.031,11 hectares (25.86%) in year 2000, and 1.148,49 hectares (28, 81%) in  year 2015. Keywords:  Change detection, land cover, interpretation, Landsat imagery